Tenurial Mapping and Agroforestry Model Development Based on Socio-Cultural Dynamic on Muria Forest Production Area - Banowati, Eva; Juhadi, Juhadi; Suhadi, Suhadi; Ramadhan, Muhammad Fauzan; Pramita, Ayu Wulansari; Wijayanti, Lina Adi; sari, Yuria; Nugraha, Satya (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
The utilization of production forest resources is still oriented towards timber production and land use conflicts, often causing conflicts of interest between local communities and Perhutani as the manager of state-owned forests. The existing environmental conditions are less conducive. This phenomenon also occurs in the Muria Forest Area, so an appropriate management strategy is needed through tenure mapping and an understanding of the socio-cultural dynamics of the local community. Data is based on the results of observations, documentation, interviews, and FGDs. Data and information are analyzed using GIS and SWOT. Data processing and tenure mapping results show a trend of fluctuating decline in the Muria Forest area, especially in the outermost areas of the Muria Forest Area, which are close to settlements. Changes in land use that vary each year can provide an overview of the dynamics of community conditions and the discretion of implementing regulations. Based on the IFAS and EFAS weight and ranking analysis, the internal factor value is positive 0.75, and the external factor is positive 0.58. The results of IFAS and EFAS show that the right strategy is the aggressive type in quadrant 1 (growth-oriented strategy). This study found eleven strategies with two main approaches: first, a strategy with an approach to associative human resources in forest management to accommodate various conflicts that arise; second, an innovative strategy that focuses on the sustainability of forest resources.